How prepared is Brazil to tackle the COVID-19 disease? (2020)
The emergence of new diseases such as Sars-Cov-2 is a reflection of the expansion of anthropic activities on natural ecosystems. Food insecurity is also a key problem that causes the ingestion of wild protein sources, causing imbalance and the contact of human populations with pathogens unknown by modern medicine and raising the importance of health care infrastructure. The first case in Brazil was reported on February 25, 2020, in the city of São Paulo; however, to date the number of confirmed cases, until May 28, 2020 nationwide was 391 222 confirmed and of 24 512 deaths, which are underestimated values due to the lack of mass tests. As a result of the city of São Paulo being a hub for several national and international transport systems, COVID-19 reached the entire Brazilian states and South American countries.